Financial wellbeing of poor households: role of digital financial inclusion - Lu, Ming-Pey; Zunarni Kosim,; Nora Azureen Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to examine determinants of financial wellbeing and the mediating effects of digital financial inclusion for poor households in Malaysian Borneo. A total of 405 responses were collected from the poor households in Sabah and Sarawak using a self-administered questionnaire. The data were analyzed using PLS modeling techniques. The findings demonstrate that financial wellbeing is significantly determined by financial behavior, financial literacy, and digital financial inclusion. However, digital literacy is not associated with financial wellbeing. Digital financial inclusion plays a mediating role in enhancing financial wellbeing. The results of multigroup analysis show that the impacts of these relationships are higher for Sarawak than Sabah. This study enriches the literature on financial wellbeing by examining determinants from broader perspectives and focusing on poor households in Malaysian Borneo, an underexplored area. The multigroup analysis shed light on the differences in the paths to financial wellbeing of poor households in Sabah and Sarawak. Policies and strategies aiming to improve financial wellbeing and accelerate digitalization for poor households should be emphasized.